Gender and disaster risk management: comparative analysis of the international and Latin American and Caribbean agendas - Fernández-Saavedra, Ana Gabriela; González-Arias, Rosario; Dema-Moreno, Sandra (Iberoamerican Journal of Development Studies, 2023)
The article carries out a comparative documentary analysis in a double sense: on the one hand, on the incorporation of the gender perspective in the main multilateral agreements on disaster risk reduction approved in the international, Latin American, and Caribbean sphere and, on the other, on the treatment of disasters risk reduction in the equality agenda in the same territorial area. The results show that there has been an accelerated process of incorporating the gender perspective in disaster risk management on a global scale, but not in Latin America and the Caribbean, a geographical context in which said evolution has not been homogeneous or constant. The lag identified in this region, especially affected by disasters, reveals the importance of having a harmonized regulation, which also incorporates the scientific evidence obtained on the matter in recent decades.
Keywords: multilateral agreements; risk management; disasters; gender; intersectional approach